The Protein Engineering of Zearalenone Hydrolase Results in a Shift in the pH Optimum of the Relative Activity of the Enzyme - Anna Dotsenko; Igor Sinelnikov; Ivan Zorov; Yury Denisenko; Aleksandra Rozhkova; Larisa Shcherbakova (Toxins)
An acidic shift in the pH profile of Clonostachys rosea zearalenone hydrolase (ZHD), the most effective and well-studied zearalenone-specific lactone hydrolase, is required to extend the range of applications for the enzyme as a decontamination agent in the feed and food production industries. Amino acid substitutions were engineered in the active center of the enzyme to decrease the pKa values of the catalytic residues E126 and H242. The T216K substitution provided a shift in the pH optimum by one unit to the acidic region, accompanied by a notable expansion in the pH profile under acidic conditions. The engineered enzyme demonstrated enhanced activity within the pH range of 3–5 and improved the activity within the pH ranging from 6 to 10. The D31N and D31A substitutions also resulted in a two-unit shift in the pH optimum towards acidic conditions, although this was accompanied by a significant reduction in the enzyme activity. The D31S substitution resulted in a shift in the pH profile towards the alkaline region. The alterations in the enzyme properties observed following the T216K substitution were consistent with the conditions required for the ZHD application as decontamination enzymes at acidic pH values (from 3.0 to 6.0).